2022
DOI: 10.3390/ma15041511
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Determination of the Transmission Efficiency of a Silica Optical Fiber Cable Using a Solar Power Tower

Abstract: After being adequately captured and concentrated, solar radiation can be conducted by optical fiber bundles/cables and directly used for illumination (lighting) or heating of confined spaces, or indirectly used by converting it in other forms of energy (e.g., for producing electricity). This article reports preliminary tests conducted on a 7-m-long optical fiber bundle/cable with an effective aperture circular area of 14 mm in diameter, specially designed and manufactured by a leading company to transmit up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[132][133][134][135] Other recent developments have also coupled incoherent concentrated solar light to fiber optics for diverse applications including photocatalysis. [136,137] That being said, upstream H 2 S to hydrogen conversion is an emerging field and requires thorough systematic theoretical and experimental studies before implementing it into industry-relevant processes.…”
Section: Discussionmentioning
confidence: 99%
“…[132][133][134][135] Other recent developments have also coupled incoherent concentrated solar light to fiber optics for diverse applications including photocatalysis. [136,137] That being said, upstream H 2 S to hydrogen conversion is an emerging field and requires thorough systematic theoretical and experimental studies before implementing it into industry-relevant processes.…”
Section: Discussionmentioning
confidence: 99%
“…More physical configuration damage will consequently result, which has an impact on the transmission length of optical cables. It is indicated that generated power must be delivered in proper proportion in order to protect the planned system from physical degradation (Rosa et al, 2022). Even though some standard parameters for fiber optic power generation have been established, the supplied power in some cases remains stable for the duration of the installation cycle.…”
Section: Existing Approachesmentioning
confidence: 99%